Integrating Local Wisdom with Technology: Designing Learning Trajectory of Cylinder through Realistic Mathematics Education Approach - Nursyahidah, Farida; Marsha Anindya, Faisa; Amalia Yulianti, Masayu; Izzati Prisanto, Zulfa; Adventino Rendra Rosario, Marcel (Mathematics Education Journal, 2025)
The study of cylindrical geometry is a fundamental component of mathematics education, yet many students face challenges in grasping the concepts of surface area and volume. To address this issue, it is imperative to design a structured learning trajectory that leverages innovative approaches and integrates suitable contextual elements with technological assistance. This study explores the implementation of Realistic Mathematics Education (RME) supported by animated videos and Adobe Animate, to facilitate understanding of these concepts. The research focuses on the design of instructional activities centered on the Semarang Nyadran tradition as a contextual framework. Employing a design research methodology, this study was conducted in three stages: preliminary design, design experimentation, and retrospective analysis. The participants were seventh-grade students at a state junior high school in Semarang. The resulting learning trajectory comprises four key activities: observing animated videos depicting the Nyadran tradition to identify cylindrical characteristics, determining the cylinder's surface area through cardboard modeling, calculating the cylinder's volume using styrofoam and 2D geometry formulae, and solving contextual problems related to cylindrical geometry. The incorporation of the Nyadran tradition, animated videos, and Adobe Animate provided a culturally relevant and technologically enriched learning experience, enhancing students' comprehension of cylindrical concepts and their ability to solve contextual problems effectively. This study highlights the potential of integrating local cultural wisdom and technology in mathematics education to create engaging, meaningful, and contextually grounded learning experiences. The findings offer insights for future research to explore other forms of local wisdom as entry points for teaching diverse mathematical topics in innovative and technology-integrated ways.